Taire ou exposer la diversité sexuelle ? Impacts des normes de genre et de l'hétéronormativité sur les pratiques enseignantes - Gabrielle Richard (Genre, Sexualité et Société)
Based on 22 interviews and 243 survey questionnaires filled out by high school teachers in Québec (Canada), this paper questions the existence of norms relating to gender and sexual orientation in schools. Results suggest that teachers’ professional practices regarding homophobia and sexual diversity are influenced by these norms, whether they identify as heterosexual or as lesbian, gay or bisexual (LGB). Thirty years after the first studies on LGB teachers’ experiences, the coming out literature remains central to the understanding of teachers’ apprehensions and fears, as well as their pedagogical practices.